Coping with increasing tides: Technological change, agglomeration dynamics and climate hazards in an agent-based evolutionary model - Alessandro Taberna; Tatiana Filatova; Andrea Roventini; Francesco Lamperti (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2021)
By 2050 about 70% of the world's population is expected to live in cities. Cities offer spatial economic advantages that boost agglomeration forces and innovation, fostering further concentration of economic activities. For historic reasons urban clustering occurs along coasts and rivers, which are prone to climate-induced flooding. To explore trade-offs between agglomeration economies and increasing climate-induced hazards, we develop an evolutionary agent-based model with heterogeneous boundedly-rational agents who learn and adapt to a changing environment. The model combines migration decision of both households and firms between safe Inland and hazard-prone Coastal regions with endogenous technological learning and economic growth. Flood damages affect Coastal firms hitting their labour productivity, capital stock and inventories. We find that the model is able to replicate a rich set of micro- and macro-empirical regularities concerning economic and spatial dynamics. Without climate-induced shocks, the model shows how lower transport costs favour the waterfront region leading to self-reinforcing and path-dependent agglomeration processes. We then introduce five scenarios considering flood hazards characterized by different frequency and severity and we study their complex interplay with agglomeration patterns and the performance of the overall economy. We find that when shocks are mild or infrequent, they negatively affect the economic performance of the two regions. If strong flood hazards hit frequently the Coastal region before agglomeration forces trigger high levels of waterfront urbanization, firms and households can timely adapt and migrate landwards, thus absorbing the adverse impacts of climate shocks on the whole economy. Conversely, in presence of climate tipping points which suddenly increase the frequency and magnitude of flood hazards, we find that the consolidated coastal gentrification of economic activities locks-in firms on the waterfront, leading to a harsh downturn for the whole economy.
Keywords: C63; Q54; Q55; R11; R12; 330; Agglomeration; path-dependency; climate; flood; shock; relocation; migration; agent-based model; tipping point; resilience; lock in